Posted by Nadia on Wednesday, October 12, 2011 at 11:36pm.
y=f(x)=x^2-x-6
The y-intercept is the value of y when x=0.
Substitute x=0 in the above equation to find the y-intercept.
The x-intercept is to find the roots of the equation, when y=0, or
f(x)=x^2-x-6=0
By factoring f(x) into
f(x)=(x-3)(x+2)
you should be able readily find the two zeroes of f(x).
If you need further help, post again.
well i know the x-intercept is (3,-2)
but i can seem to understand y intercept. I thought it would be (0,0) but it was wrong
The y-intercept is where the graph crosses the y-axis, that is, where x=0.
In this case, f(0) = 0 - 0 - 6 = -6, so the y-intercept is (0,-6)
Also, there are two x-intercepts: (3,0) and (-2,0). They are the points where the graph crosses the x-axis, not just the x-values.
Thank you!!